Analisis Usability Sistem Komputerisasi Haji Terpadu Palembang Menggunakan Metode System Usability Scale (SUS) - Abdurrahman Abdurrahman; Maria Ulfa (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
The Palembang Integrated Hajj Computerized System which is currently used as an information system for Hajj and Umrah pilgrims, because the entire data processing process for the purpose of making Hajj documents such as passports, departure and return flights, banking and biodata of prospective pilgrims refers to the integrated computer system. Both internally and externally there has never been an evaluation, either at the time of design, manufacture or implementation. This research was conducted with the title "Usability Analysis of the Palembang Integrated Hajj Computerized System Using the System Usability Scale (SUS) Method". Aims to measure the level of usefulness of the Palembang Siskohat Application and test the validity and reliability using SPSS 24. System Usability Scale (SUS) With 16 questions as a benchmark for assessing the application. 30 respondents were selected among the administrative staff of the Hajj and Umrah pilgrims in Palembang. The results of the usability test showed the value of Learnibilty 4.68, Efficiency 4.46, Memorabilty 4.64, Error 3.34 Satisfaction 3.74, the average usability value was expressed by Very good reliability and validity on each variable indicate that the questionnaire for each variable has a fairly good level of reliability.